Theoretical investigation of electronic, magnetic and magnetocaloric properties of Bi25FeO40 compound. (3rd April 2021) - Jebari, H.; Tahiri, N.; Boujnah, M.; El Bounagui, O.; Taibi, M.; Ez-Zahraouy, H.
ABSTRACT: The electronic, magnetic and magnetocaloric properties of the Iron-Selenite Bi25 FeO40 compound have been investigated using first-principles calculations and Monte Carlo simulations (MCs). It was found that Bi25 FeO40 is a p -type semiconductor with an indirect bandgap of about 2.16 eV which is in good agreement with the previous experimental and theoretical results. The studied compound displays a ferromagnetic behaviour with a spin moment of the unit cell of about 4.06 μB . The Bi25 FeO40 compound exhibits a weak ferromagnetic behaviour around TC  = 271.96 K; this value is in good agreement with experimental results. In addition, it shows a magnetocaloric effect (MCE) around the Curie temperature ( TC ), with the maximum values of the magnetic entropy change ( Δ S m M a x ) and relative cooling power (RCP) are 2.56 J.kg −1 .K −1 and 55.01 J/Kg, respectively, under applied an external magnetic field of h  = 5.00 T. The good magnetocaloric properties reveal the applicability of Bi25 FeO40 compound to the magnetic refrigeration around TC .